The effect of immersive experience, user engagement and perceived authenticity on place satisfaction in the context of augmented reality - Dag, Kazim; Cavusoglu, Sinan; Durmaz, Yakup (EMERALD GROUP PUBLISHING LTD)
PurposeThis study aims to measure the effect of augmented reality (AR) on immersive experiences, place satisfaction, user engagement and perceived authenticity.Design/methodology/approachThe population of the research consists of museum visitors visiting the Sakip Sabanci Museum in Turkey, which provides an interactive experience to the audience using AR technology via iPads. The data were collected both online and offline. The research was carried out with 397 questionnaire forms. The hypotheses were tested through smart partial least squares (PLS) 3.FindingsImmersive experience positively affects place satisfaction, user engagement and perceived authenticity. It was also concluded that user engagement and perceived authenticity mediated the relationship between immersive experience and place satisfaction.Research limitations/implicationsThe entire universe could not be reached, as the study had limitations in terms of time, cost, accessibility and control difficulties. Therefore, the study was carried out with 397 visitors who visited the Sakip Sabanci Museum (SSM) in Turkey and used AR technology.Practical implicationsThe study emphasized the importance of AR in cultural tourism. The interactions of museum visitors with AR can be greatly enhanced by immersive experiences. Expanding AR to provide different experiences can increase the number of visitors.Originality/valueAlthough there are recent studies on AR, it seems insufficient to investigate and empirically examine this subject in the context of museums. No studies conducted in Turkey have investigated the current topic of this study. Conducting this research in Turkey with the proposed research model will make the topic easier to understand, proving the study's originality.
Keywords: Perceived authenticity; User engagement; Place satisfaction; Immersive experience; Augmented reality